El papel de la DEA en la emergencia del campo policial antidrogas en América Latina - Pérez Ricart, Carlos A. (El Colegio de México A.C., 2017)
In this paper we examine the institutional responses that emerged in Latin America to drug trafficking in the 1970s. It explores, in particular, the emergence of the field of counternarcotics policing at the time. As a central argument, it asserts that US drug agencies—especially the Drug Enforcement Administration (DEA)—helped to structure the field of counternarcotics policing in Latin America. Based on a review of a range of documentary resources, we analyze the origins of counternarcotics institutions in Latin America, the dissemination of institutional development practices undertaken by the DEA, and the creation of police networks in the region.